Perancangan Aplikasi Pertokoan Berbasis Desktop di Pets Shop Store - Riza Qurrota Ayun riza; Kiky Zulkifli (Asosiasi Dosen Akuntansi Indonesia, 2026)
The rapid development of information technology has provided many conveniences in various fields, including trade and services. Pets Shop Store is an MSME engaged in the sale of various types of pet food and pet supplies, located on Jalan Sumber Kedawung, Leces, Probolinggo Regency. Pets Shop Store still records sales, purchases, and inventory manually, which often causes recording errors, report delays, and difficulties in data retrieval. This study aims to design a desktop-based retail application to support transaction management and inventory control. The system development method used is the System Development Life Cycle (SDLC) Waterfall model, which includes analysis, design, implementation, testing, and maintenance stages. The application was developed using Microsoft Visual FoxPro 9.0. The results of this study indicate that the designed retail application is able to improve transaction efficiency, enhance data recording accuracy, and facilitate the preparation of sales, purchase, and financial reports.